Curbing boredom in online teaching: Effects of an autonomy-oriented intervention with EAP students - Rezaee, Abbas Ali; Seyri, Haniye (Frontiers in Psychology, 2022)
Despite the growing body of research on boredom and its causes in face-to-face classes, little is known about how pedagogical interventions can mitigate this negative emotion. The purpose of this study was to examine boredom experienced by EAP students in online classes and investigate the effects of an autonomy-oriented intervention program on students’ boredom. The boredom scale was administered to 84 students before and after the autonomy-oriented intervention. By designing and implementing autonomy-oriented intervention based on the autonomy enhancement model, positive results were obtained with reduced levels of boredom. The results revealed that the intervention was effective and boredom was reduced to a noticeable extent. In addition, the qualitative results contributed to our understanding of the learners’ experiences throughout the intervention. We conclude the study with implications for EAP instructors to employ different pedagogical interventions to mitigate negative emotions in online EAP classes.